Influence of diabetes on the efficacy of DL-3-n-butylphthalide in post-stroke cognitive impairment: a 12-month prospective cohort study - Lu, Yuting; Wang, Lifeng; Hao, Juan; Song, Jingjing; Fan, Chenxi; Ning, Xianjia; Wang, Jinghua; Li, Yan (Frontiers in Aging Neuroscience, 2025)
ObjectiveDiabetic chronic hyperglycaemia amplifies oxidative stress, microvascular injury, and insulin-resistant neuroinflammation, counteracting the pro-angiogenic, mitochondrial-protective, and anti-apoptotic effects of DL-3-n-butylphthalide (NBP). It remains unknown whether glycaemic status modulates the long-term cognitive benefits of NBP after ischaemic stroke (IS). This study compared 12-month efficacy of NBP on cognition between non-diabetic and diabetic patients with subacute IS.MethodsWe conducted a community-based prospective cohort study involving 594 patients who had an ischemic stroke 1–6 months prior and no baseline cognitive impairment. Participants were assigned to either the NBP treatment group or the usual care group. MMSE scores were assessed at baseline and 12 months. The primary outcomes were ΔMMSE, its percentage change, and incident cognitive decline (≥3-point MMSE reduction). Separate multivariable regression analyses were conducted for non-diabetic and diabetic subgroups.ResultsIn non-diabetic patients (n = 360), NBP reduced the risk of cognitive decline by 45% (RR = 0.55, 95% CI 0.31–0.98, p = 0.043) and preserved language performance (β = −0.27, 95% CI –0.51 to −0.03). Among participants with diabetes (n = 234), NBP did not significantly lower decline incidence (RR = 0.63, 95% CI 0.33–1.19, p = 0.151), yet modestly improved orientation (β = −0.53, 95% CI –1.05 to −0.001, p = 0.045). Domain-specific analyses showed that NBP protected language in non-diabetic patients and orientation in diabetic patients (p < 0.05), while ΔMMSE was superior to control in both strata.ConclusionIn non-diabetic patients with subacute IS, NBP exerts more pronounced protective effects on overall cognition and language. In contrast, in diabetic patients, only a slight improvement in orientation is observed. Clinically, it is essential to prioritize optimization of diabetes management based on blood glucose control status before considering the addition of NBP. Further validation of these exploratory findings is warranted through larger-scale randomized trials.